2019
DOI: 10.20452/pamw.4424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term fluctuations in outdoor air pollution on the number of hospital admissions due to acute myocardial infarction among inhabitants of Krakow, Poland

Abstract: In Poland, the limits set by the World Health Organization (WHO) for the levels of particulate matter (PM) are far exceeded, which constitutes a major problem. The main source of PM is low-stack emission (ie, emission from residential and small-industry chimneys below the level of 40 m above ground), and to a lesser extent, transport and other sources. 2 The highest PM concentrations are observed during the heating season, especially when people use low-quality coal and INTRODUCTION Both indoor and outdoor air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
14
1
Order By: Relevance
“…Dysfunction of coronary microcirculation is associated with increased risk of major adverse cardiovascular events including cardiac death, stroke, and heart failure [6,7]. Chronic inflammation is considered as an important factor in pathophysiology of atherosclerosis [8][9][10]. Elevated level of inflammatory markers is observed in disease of epicardial arteries [11,12].…”
Section: Neutrophil-lymphocyte Ratio and Platelet-lymphocyte Ratio As Predictors Of Coronary Microcirculatory Disease Occurrence And Outcmentioning
confidence: 99%
“…Dysfunction of coronary microcirculation is associated with increased risk of major adverse cardiovascular events including cardiac death, stroke, and heart failure [6,7]. Chronic inflammation is considered as an important factor in pathophysiology of atherosclerosis [8][9][10]. Elevated level of inflammatory markers is observed in disease of epicardial arteries [11,12].…”
Section: Neutrophil-lymphocyte Ratio and Platelet-lymphocyte Ratio As Predictors Of Coronary Microcirculatory Disease Occurrence And Outcmentioning
confidence: 99%
“…e modelling results indicate that air pollution causes 2800 deaths a year in Warsaw [32]. Moreover, in epidemiological studies conducted in Cracow by Konduracka et al a correlation was found between air pollution with PM 2.5 and the incidence of myocardial infarction [33].…”
Section: Discussionmentioning
confidence: 95%
“…Time-series analyses of PM-related morbidity in Poland are still rare and, to the authors' knowledge, until the end of 2021, no paper was published that included an analysis of the risk of hospitalizations with the use of GAM models. Several studies have applied other time-series methods to calculate air-pollution-related morbidity risks in individual cities [37][38][39], single voivodeships [40] or several selected locations [41][42][43][44][45], but none of them included a multi-city meta-analysis.…”
Section: Discussionmentioning
confidence: 99%